Festa e Turismo Religioso: a procissão em louvor ao Nosso Senhor dos Passos na cidade de São Cristóvão (Sergipe - Brasil) (Feast and Religious Tourism) - DOI: 10.5752/P.2175-5841.2011v9n20p96 - Aragão, Ivan Rêgo (Horizonte, 2011)
The feasties held by the Catholic Church were the first social events during the period of colonial Brazil, bringing people from different social classes, merging the different cultures and ethnicities. These were the subject of harmony, but also of struggles and social control held by the Church and the Portuguese State. Currently in Brazil, the Catholic party moving a lot of people in the period of their events. Apart from tourist attractions, religious celebrations in the country are also intangible heritage and culture are embedded within "the feast" of Brazilians. This present article seeks to address aspects of the Procession of "Nosso Senhor dos Passos" the city of São Cristóvão state of Sergipe. The methodology used was literature, with discussion in the theoretical field of Baroque, Devotional Feast, Tradition, Religion, Procession, Religious Tourism, Culture and Identity. We also carried out field research, with direct observation.With this study, it was noticeable that, as distant territory of Portugal, the religious feasties in Brazil have taken a very dynamic, absorbing the profane elements and reframing through popular appeal.